Immunosuppression in pediatric liver transplant recipients: Unique aspects. Issue 2 (17th January 2017) - Miloh, Tamir; Barton, Andrea; Wheeler, Justin; Pham, Yen; Hewitt, Winston; Keegan, Tara; Sanchez, Christine; Bulut, Pinar; Goss, John
Abstract : Pediatric liver transplantation has experienced improved outcomes over the last 50 years. This can be attributed in part to establishing optimal use of immunosuppressive agents to achieve a balance between minimizing the risks of allograft rejection and infection. The management of immunosuppression in children is generally more complex and can be challenging when compared with the use of these agents in adult liver transplant patients. Physiologic differences in children alter the pharmacokinetics of immunosuppressive agents, which affects absorption, distribution, metabolism, and drug excretion. Children also have a longer expected period of exposure to immunosuppression, which can impact growth, risk of infection (bacterial, viral, and fungal), carcinogenesis, and likelihood of nonadherence. This review discusses immunosuppressive options for pediatric liver transplant recipients and the unique issues that must be addressed when managing this population. Further advances in the field of tolerance and accommodation are needed to relieve the acute and cumulative burden of chronic immunosuppression in children. Liver Transplantation 23 244–256 2017 AASLD